An in situ and real time study of the formation of CdSe NCs. Issue 45 (18th November 2020) - Palencia, Cristina; Seher, Robert; Krohn, Jan; Thiel, Felix; Lehmkühler, Felix; Weller, Horst
Abstract : In situ studies are crucial to demonstrate that magic-size clusters are always intermediates in the formation of regular NCs. Abstract : Magic Size Clusters (MSCs) have been identified in the last few years as intermediates in the synthesis of nanocrystals (NCs), and ever since there has been increased interest in understanding their exact role in the NC synthesis. Many studies have been focused on understanding the influence of precursors or ligands on the stability of MSCs and on whether the presence of MSCs influences the reaction pathway. However, their kinetic nature calls for an in situ temporal evolution study of the reaction, from the first seconds until the formation of regular nanocrystals, in order to unravel the role of MSCs in the formation of NCs. We have studied the synthesis of CdSe nanocrystals (NCs) in a continuous-flow reactor with in situ optical and small angle X-ray scattering characterization (SAXS). Our results show that MSCs are always formed, regardless the temperature, as necessary intermediates in the formation of CdSe NCs, and that their accumulation in solution depends only on the reaction time. These results explain why MSCs were, in some cases, not observed in some previous studies.